1985
DOI: 10.1159/000180043
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Levels of Pituitary and Steroid Hormones in Ovine and Human Ovarian Follicular Fluid

Abstract: Changes in the protein and steroid hormones of follicular fluid, aspirated from different follicles of sheep and human ovaries, have been measured and correlated with the size of the follicles. As the fluid contains a number of proteins, steroids have been measured directly and after ether extraction. The follicular fluid concentrations of progesterone and 17β-oestradiol measured directly in the fluid increased with the size of the follicles. The levels of free testosterone remained constant in all sizes of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…steroids, gonadotrophins or growth factors. All previous in-vitro follicular fluid studies reported endocrine data from cross-sectional studies of groups of follicles considered to be at the same stage of development because of a similarity in size (Bomsel-Helmreich et al, 1979;McNatty et al, 1979;Brailly et al, 1981;McNatty, 1981;Testart et al, 1983;Shailaja et al, 1985;Westergaard et al, 1986;Magoffin, 1992, 1993). There are two main drawbacks to this approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…steroids, gonadotrophins or growth factors. All previous in-vitro follicular fluid studies reported endocrine data from cross-sectional studies of groups of follicles considered to be at the same stage of development because of a similarity in size (Bomsel-Helmreich et al, 1979;McNatty et al, 1979;Brailly et al, 1981;McNatty, 1981;Testart et al, 1983;Shailaja et al, 1985;Westergaard et al, 1986;Magoffin, 1992, 1993). There are two main drawbacks to this approach.…”
Section: Discussionmentioning
confidence: 99%
“…This high precision has led to a more accurate assessment of the chronological endocrine events during the mid-to late follicular phase (Ahmed Ebbiary et al, 1994). On the other hand, all in-vitro studies lack this precision and endocrine data from pooled follicular fluid obtained from several follicles have been reported (Bomsel-Helmreich et al, 1979;McNatty et al, 1979;Gwatkin, 1980;Brailly et al, 1981;McNatty, 1981;Nilsson et al, 1982;Testart et al, 1983;Lenton et al, 1985;Shailaja et al, 1985;Westergaard et al, 1986;Xiao and Xiao, 1989;Magoffin, 1992, 1993). More recent in-vivo studies have described the follicles following the LH surge or the administration of human chorionic gonadotrophin (HCG) to time endocrine events, and thus offer only an assessment of the luteinized late preovulatory follicle (Bomsel-Helmreich, 1983;Marrs et al, 1984;Lobo et al, 1985;Templeton, 1985;Lenton et al, 1988;Stone et al, 1988;Siebel et al, 1989;Westergaard and Andersen, 1989;Tonetta et al, 1990;Andersen, 1991;Andersen et al, 1993).…”
Section: Discussionmentioning
confidence: 99%